Breaking the cycle: a comprehensive exploration of topical steroid addiction and withdrawal - Maskey, Anish R.; Sasaki, Akimi; Sargen, Manuel; Kennedy, Maureen; Tiwari, Raj K.; Geliebter, Jan; Safai, Bijan; Li, Xiu-Min (Frontiers in Allergy, 2025)
Topical steroid withdrawal (TSW) is a skin condition characterized by red burning, itchy, painful skin lesions, often accompanied by peeling, and cracking. Patients experience sleep disturbances due to intense itching, significantly impacting their quality of life. A majority of affected individuals develop secondary bacterial infection, marked by heavy colonization of Staphylococcus aureus (S. aureus) and alterations in the skin microbiome. TSW is described as a rebound effect following discontinuation of prolonged use of mid-to-high-potency topical corticosteroids. There exist no definitive diagnostic criteria for this entity, and it is often misdiagnosed as a flare-up of an underlying condition or a contact allergy. Despite numerous personal reports and experiences shared on online platforms, studies on TSW remain scarce in scientific literature. Recognizing and effectively managing this condition is critical for healthcare providers seeking to develop comprehensive management plans. These plans typically include supportive therapy for both physical and psychological symptoms, as well as the gradual tapering of corticosteroid use before complete discontinuation. This review aims to consolidate the existing knowledge on TSW, providing a comprehensive resource for its identification, management, and treatment. By enhancing understanding of TSW, this review seeks to support healthcare providers in implementing optimal management strategies and improving patient outcomes.